Median lethal concentration of formaldehyde and its genotoxic potential in bullfrog tadpoles (Lithobates catesbeianus) - Santana, Juliana M.; Dos Reis, Adriana; Teixeira, Patrícia C.; Ferreira, Fábio C. [UNESP]; Ferreira, Cláudia M. (Taylor & Francis, 2015)
In order to avoid that contaminated frog farms animals escaping in the environment and become potential vector of emergent diseases, studies with disinfection protocol are strictly necessary. The formaldehyde is one of the compounds tested in fungal disinfection protocols and also used in aquaculture. This study aimed to determine the median lethal concentration (LC50–96h) of formaldehyde in bullfrog tadpoles and to evaluate the possible genotoxic effects in acute exposition. Accordingly, the animals were exposed to formaldehyde in the concentrations of 6, 9, 12, 15, and 18 mg L−1, and after 96 h blood samples were drawn for the micronucleus (MN) test. The LC50–96h was 10.53 mg L−1, and the MN frequency increased in proportion to the formaldehyde concentrations, with an estimated frequency in the negative control being 1.35 MN/individual. We concluded that formaldehyde is genotoxic to tadpoles of bullfrogs in the tested concentrations, and the choice of this chemical should be contemplated before its use in animals in captivity.
Keywords: amphibians; bullfrog farm; Chytridiomycosis; micronucleus